Repair of 3-methylthymine and 1-methylguanine lesions by bacterial and human AlkB proteins - Falnes, Pål Ø. (Oxford University Press, 2004)
The Escherichia coli AlkB protein repairs 1-methyladenine (1-meA) and 3-methylcytosine (3-meC) lesions in DNA and RNA by oxidative demethylation, a reaction requiring ferrous iron and 2-oxoglutarate as cofactor and co-substrate, respectively. Here, we have studied the activity of AlkB proteins on 3-methylthymine (3-meT) and 1-methylguanine (1-meG), two minor lesions which are structurally analogous to 1-meA and 3-meC. AlkB as well as the human AlkB homologues, hABH2 and hABH3, were all able to demethylate 3-meT in a DNA oligonucleotide containing a single 3-meT residue. Also, 1-meG lesions introduced by chemical methylation of tRNA were efficiently removed by AlkB. Unlike 1-meA and 3-meC, nucleosides or bases corresponding to 1-meG or 3-meT did not stimulate the uncoupled, AlkB-mediated decarboxylation of 2-oxoglutarate. Our data show that 3-meT and 1-meG are repaired by AlkB, but indicate that the recognition of these substrates is different from that in the case of 1-meA and 3-meC.